(untitled) (Web of Teachers: Inderscience Research, 2024)
The article reveals the role of bioinformatics in the development of biological sciences, in particular genetics, genomics and transcriptomics. The role of bioinformatics as a science is described, which includes the creation and application of computational tools, algorithms, databases for storing, extracting, managing and analyzing biological information